Geotechnical monitoring of the Carrapateena cave - Poulter, M; Ormerod, T; Balog, G; Cox, D (Caving 2022: Fifth International Conference on Block and Sublevel Caving, 2022)
Carrapateena is a copper-gold deposit hosted in a brecciated granite complex, located 460 km north of Adelaide, South Australia. The deposit is currently mined using the sublevel cave (SLC) mining method, with future mining to incorporate a block cave footprint beneath the SLC. The ore is located below 500 m of unmineralised rock cover. Monitoring of the cave is a critical activity at Carrapateena, in order to understand the cave geometry, and effectively manage geotechnical risk related to cave propagation (air blast and subsidence). The SLC has no overlying monitoring level underground, and as such all monitoring is conducted remotely, or from surface. The cave monitoring system incorporates many different tools and techniques in order to reduce the uncertainty related to cave back interpretation. The critical analysis methods used in cave monitoring and interpretation at Carrapateena are: Networked Smart Markers (Elexon), Cave Tracker Beacons (Elexon), open hole camera surveys into the cave, active seismic tomography, a dense array of microseismic sensors around the cave back to monitor cave-related seismicity, and utilisation of volumes mined from the cave, to facilitate mass balance analyses. There have been many learnings throughout the time the Carrapateena cave has been monitored. Firstly, the certainty provided by physically inspecting both the cave back and muckpile through a camera in an open hole, is currently, and in the opinion of the authors, the most valuable monitoring tool for cave back and airgap interpretation out of all the tools in place at Carrapateena. Contingency in the form of multiple holes should be accounted for in design. Secondly, defined limits and forward planning is required for when surface restrictions will be necessary due to potential subsidence, to allow time to convert any monitoring systems to remote setups. Ideally, this functionality could be incorporated from the beginning. Lastly, thorough analysis should be undertaken prior to installing monitoring systems to understand the most likely cave shape and potential propagation. Monitoring arrays should be treated holistically as a combined monitoring system, instead of individual systems, with an understanding of the risks associated with each, and the resulting uncertainty for various areas that will be monitored.
Keywords: caving; cave monitoring